Thyroid abscess: respiratory and high alimentary canal obstruction - Carriquiry, Luis A; Piñeyro, Alberto; Aizen, Bernardo; Parodi, Hernán (Cirugía del Uruguay, 1983)
The authors present a case of thyroid abscess taking place in a nodular gbiter relapse, that began with a fast enlargement of the P,ter and the onset of respiratory and high alimentary canal obstructive symptomatology. They point out the importance of evacuating puncture that made the diagnosis and rel ie v e t he acute sympomatology, allowing the setting up of antibiotic treatment. They recommend the primary surgical scission of the goiter absceded that they performed with good results.